Wind forcing of sea level variability in a tropical coral reef area in the western Gulf of Mexico - Román Rodolfo Vera-Mendoza (Latin American Journal of Aquatic Research, 2017)
Sea level, water temperature, and wind stress data were obtained from the Western Gulf of Mexico to elucidate the relationship between sea level changes and meteorological variables in a tropical coral reef system. Sea level and water temperature data were measured with a series of acoustic Doppler current profilers anchored at a depth of approximately 13 m in the Veracruz Reef System. The barometric and wind stress data were obtained from an automatic coastal weather station. Principal Component Analysis w as applied to the series to determine the relative influence of the different meteorological variables on sea level. The seasonal variability of sea level is evident in the year - long data (September 2008 to April 2010) with a thermal expansion during the s ummer. Barometric pressure was found to be the second strongest forcing mechanism of sea level variability and not the first one. Opposite to what would be expected in protected coastal areas where the wind forcing mechanism on sea level may not be as impo rtant. The local winds were the main forcing mechanism of the sea level variability from March to September, while the meridional winds were more important than local winds from October to February.